E-Sport in Education: A Systematic Review of Enhancing EFL Learning through Competitive Gaming Activity: English - Ni Luh Putu Devi Puspitasari; Made Hery Santosa (Journal of English Development, 2024)
The rapid rise of e-sports in recent years has prompted educators to explore its potential as a tool for enhancing learning. This systematic review aims to investigate the impact of e-sports on developing cognitive, social, and technical skills among students. A comprehensive literature search was conducted on academic databases such as Google Scholar, Scopus, and Web of Science, covering studies published between 2019 and 2024. The inclusion criteria were research article discussing the use of e-sports in education and its impact on student skills, written in English of the national language. After removing duplicates, titles and abstracts were screened, and eligible article were then reviewed in their entirety to extract relevant data. The results indicate that participation in competitive gaming can enhance problem-solving abilities, critical thinking, teamwork, communication, and digital literacy. However, challenges such as accessibility for students with cognitive impairments and potential negative health impact mush be addressed. Despite these challenges, the findings suggest that with careful implementation, e-sport can be a valuable addition to traditional educational methods. Future research should focus on long-term impacts and optimal integration strategies to maximize the educational benefits of e-sports.